1983
DOI: 10.1111/j.2042-7158.1983.tb02932.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of polymorphism, particle size and compression pressure on the dissolution rate of phenylbutazone tablets

Abstract: The dissolution rate of phenylbutazone from tablets after disintegration has been used to determine whether the drug particles underwent crushing or bonding during compression. Two polymorphic forms of the drug were used and the predominant effect for high drug concentration (60%), during compression was dependent upon the original particle size of the drug and its polymorphic form. With a low drug concentration (10%) in the tablet, the diluent protected the drug particles from bonding together. The particle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Tuladhar et al described the change in the API particle size during compression was affected by nature of the diluents present in the formulation and also found that the agglomeration of fine particles during compression was independent of rate compression. 95 Highly homogenous blend for highly cohesive micronized API can be achieved by blending the formulation with highly porous and freely flowing diluents. However, some diluents with highly indented surface may entrap the micronized drug and forms pockets of agglomerates which hamper the dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…Tuladhar et al described the change in the API particle size during compression was affected by nature of the diluents present in the formulation and also found that the agglomeration of fine particles during compression was independent of rate compression. 95 Highly homogenous blend for highly cohesive micronized API can be achieved by blending the formulation with highly porous and freely flowing diluents. However, some diluents with highly indented surface may entrap the micronized drug and forms pockets of agglomerates which hamper the dissolution.…”
Section: Introductionmentioning
confidence: 99%